The cranial instrument port in arthroscopy of the canine shoulder joint - Riener, S.; Lehmann, K.; Lorinson, D.; Skalicky, M. (Veterinary and Comparative Orthopaedics and Traumatology, 2009)
We describe the creation of a cranial instrument portal for shoulder joint arthroscopy in the dog using a target device that has been successfully employed for the caudal access. We compared the method with a conventional triangulation technique. The shoulder joints of 60 dog cadavers were investigated by arthroscopy and the two methods were compared on the basis of pre-defined parameters of outcome. Time, the number of trials, success, damage to cartilage and the accessibility of intra-articular structures were assessed. The anatomical localisation of the working cannula in muscles was also documented. In general, the new method permitted more successful insertion of the working cannula. This was achieved in a shorter period of time and was associated with fewer insertion attempts as well as less damage to joint cartilage. Intra-articular structures could be readily approached through the working cannula with both methods. Predetermined, clinically relevant points were comparatively more accessible with the new technique. Independent of the method, in only a few cases, the working cannula perforated neither muscles nor tendons when accessing the joint. It may be concluded that the new method using a target device is simpler and safer and offers a standardised technique to establish a cranial instrument port.
Keywords: Arthroscopy; shoulder joint; cranial instrument port; target device; dog